Report of the First Case of Candida auris Identified in Jordan - Jamal Wadi Al-Ramahi; Rola Ali Ghanem; Omar Helmy Sayyouh; Dima Al-Jammal; Mayar M. Said; Salwa Nasrat; Mona El-Shokry; Mahmoud Gazo; Tamer Saied Osman (Microbiology Research, 2023)
Candida auris (C. auris) is an opportunistic budding yeast that has been identified across 41 countries, including several countries in the Middle East. The increasing global concern stems from the pathogen’s acquired resistance to antifungal drugs and its ability to form biofilms, which allows it to survive on hospital surfaces and medical devices for up to 14 days, compromising infection prevention measures in hospitals. In this report, we present the first (reported) case of C. auris isolated from a urine sample from a 48-year-old female living in Jordan. The patient succumbed to illness five days following admission to hospital. The isolate was identified retrospectively through the national surveillance system in Jordan and was confirmed by real-time PCR. Antifungal susceptibility was carried out using the microbroth dilution technique and the isolate was found to be susceptible to all tested antifungal drugs. Overall, the report emphasizes the need for active surveillance for the rapid identification of high-risk patients colonized with C. auris. It also stresses the importance of understanding the inter-clade difference in the susceptibility pattern of C. auris to facilitate the development of preventive and therapeutic strategies.